The impact of the new public management reforms on political control and corruption : the case of Malawi's Local Governance - Tambulasi, Richard Ignitious Chipopopo (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2005.